2018
DOI: 10.1177/1933719117746761
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Regulation of Retinoic Acid Receptor Responders in the Human Placenta

Abstract: RARRES1, 2 and 3 are expressed in the functional compartments of the human placenta and can be regulated by RA. We hypothesize that the epigenetic suppression of trophoblast RARRES1 and RARB expression and the upregulation of RARRES1 in PE trophoblast cells suggest an involvement of environmental factors (eg, maternal vitamin A intake) in the pathogenesis of this pregnancy complication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 83 publications
1
24
1
Order By: Relevance
“…Our previous human studies indicated a dysregulation of the tumor suppressor genes retinoic acid receptor responsive proteins (retinoic acid receptor responders, RARRES) 1 and 2 in the third trimester placentas complicated by preeclampsia (PE) and PE conjoined with intrauterine growth restriction (IUGR) [1,2]. We observed an induction of RARRES1 expression in primary villous cytotrophoblasts isolated from PE and PE/IUGR placentas with a concomitant increase in RARRES1 syncytial staining.…”
Section: Introductionmentioning
confidence: 77%
“…Our previous human studies indicated a dysregulation of the tumor suppressor genes retinoic acid receptor responsive proteins (retinoic acid receptor responders, RARRES) 1 and 2 in the third trimester placentas complicated by preeclampsia (PE) and PE conjoined with intrauterine growth restriction (IUGR) [1,2]. We observed an induction of RARRES1 expression in primary villous cytotrophoblasts isolated from PE and PE/IUGR placentas with a concomitant increase in RARRES1 syncytial staining.…”
Section: Introductionmentioning
confidence: 77%
“…Aberrant PIWI proteins, which interact with pi-RNAs to drive post-transcriptional gene regulation, have been found in cancers (Wang et al, 2016), and theoretical evidence from piRNA evolution suggests a role in placentation, although this has yet to be proven empirically (Chirn et al, 2015). In the offspring genome, proteinuria showed an association with placental gene RARB , or retinoic acid (RA) receptor beta (rs4241542, OR 0.26 ± 0.14, p=7.04×10 −6 , MAF 0.21) (Comptour et al, 2016, Huebner et al, 2018), while the strongest association with proteinuria is on a different region, in a SNP intronic to STK32B (rs62297274 (OR 0.35 ± 0.12, p=3.5104×10 −6 ; Supplementary Table 13; Supplementary Figure 32-33). Interestingly, the minor allele for SNP rs62297274 is found at high frequencies in Peruvians compared to other global populations.…”
Section: Resultsmentioning
confidence: 99%
“…RA signaling is essential for healthy placental and fetal development in animal models, with evidence of similar requirement in humans (reviewed in (Comptour, et al, 2016)). RARB is expressed in the extravillous part of the placenta and its activation induces RARRES, shown in one study to be overexpressed in preeclamptic placentas (Huebner, et al, 2018). Our study adds to this body of literature and highlights the role of RA in proper placentation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggested that RARRES1 was involved in the apoptosis of tumor cells, inhibited the proliferation and invasion of tumor cells (42), and placenta formation might share some molecular processes of tumor (43). Studies indicated that RARRES1 was an important regulator of trophoblast cells (44), and its overexpression in trophoblast cells was highly correlated with the onset of preeclampsia (45). There were also reports that RARRES1 in ectopic endometrium of patients with endometriosis was higher than endometrium infertile women of childbearing age, prompting its potential role in endometrial differentiation (46).…”
Section: Discussionmentioning
confidence: 99%
“…the endometrium. As another component of the Notch signaling pathway (45), we speculated that the above changes might be due to the effect of hCG on the Notch signaling pathway in endometrium (49). GC has a strong immunomodulatory and antiinflammatory effect, and is used to treat autoimmune diseases and some malignant lymphomas (52).…”
mentioning
confidence: 99%